CARACTERIZAÇÃO MINERALÓGICA POR DIFRAÇÃO DE RAIOS X E O MÉTODO DE RIETVELD DA FRAÇÃO ARGILA DE UM LATOSSOLO VERMELHO DISTRÓFICO EM TRÊS MANEJOS DIFERENTES - Gonçalves, Daniele (2008)
Every day becomes more intense the demand by management to preserve or improve the quality of soil, those related to organic and mineralogical composition, in order to obtain greater productivity, minimizing the environmental impacts caused, targeting sustainable agriculture. The objectives this work were to carry out elementary chemical analysis with the X-Ray Fluorescence (XRF) and to identify the minerals of samples of a Red Latosol from Ponta Grossa, Paraná, Brazil, with the techniques of Fourier Transform Infrared (FTIR) and X-Ray Diffraction (XRD), characterizing and quantifying, by XRD and the Rietveld Method (RM), the fraction clay mineralogy of that soil, correlating it with three different managements – conventional tillage, minimum tillage and no-tillage – in three different depths: 0.0 to 0.20 m; 0.20 to 0.40 m; 0.40 to 0.60 m, by the comparative study, check the influences of the application by 24 years of these different managements on the mineralogical composition of fraction clay soil studied. The XRF data show the predominance of Al; Si; Fe; Ti for samples of soil without physical fractionation. Through FTIR and XRD there has been qualitatively in samples of soil without physical fractionation, the presence of eleven minerals: halloysite (Ha); kaolinite (Ca); montmorillonite (Mt); gibbsite (Gb); goethite (Gt); quartz (Qz); anatase (An); rutile (Rt); vermiculite (Ve); hematite (He) and magnetite (Mg) and for the fraction clay, twelve minerals: Ha; Ca; Mt; Gb; Gt; Qz; An; Rt; Ve; He; calcite (Calc) and Mg, observing variations not significant as to the presence or absence of minerals between the samples. By quantifying performed by RM, it was found in samples of fraction clay, a predominant presence of minerals: Gb; Ca; Ha; He and An being the minerals Rt; Ve and Mt those who had lower percentage by weight. The values of S in all refinements were between 4,91 and 6,27, and there was the interference of Mt the results of refinement. Both qualitatively and quantitatively small variations occurred on minerals of a sample to another, although not so expressive, not ensuring that the management did not interfere over the 24 years of its use, the mineralogy of the fraction clay of soil studied.